Dental caries status in deciduous and permanent dentition of Brazilian children aged 6-8 years with a socioeconomic base - Denise M. P. Spolidorio; José F. Höfling; Daniella Moreira; Janaina A. de O. Rodrigues; Marcelo F. G. Boriollo; Edvaldo A. R. Rosa (Universidade Estadual de Campinas, 2015)
A total of 120 children, aged 6-8 years, with different socioeconomical status (A, B and C categories) of high, middle and low class, respectively, were selected for a dental examination and data on possible variables for dmft(s) and DMFT(S) were obtained to predict the risk of caries development. Variation on dmft(s)/DMFT(S) was accounted for by the effect of some variables with a socioeconomic base. A representative part of the population in this study, particularly among the lower socioeconomic status group, was considered the highest risk group for developing dental caries. Among the parameters employed to identify such high risk populations only dmft(s) showed statistically significant differences for each socioeconomic status. The data obtained in our studies also showed that the second inferior deciduous molar followed by the first inferior deciduous molar, second molar and first superior molar respectively, were the major teeth showing high scores of dental decay. In the permanent dentition, the lesion is more often observed in the first inferior molar. In the primary dentition the inferior deciduous molars seems to be more susceptible to dental caries, followed by the superior deciduous molars, with the occlusal surface the most harmed by this pathology.